Two numbers differ by 3. The sum of their reciprocals is seven tenths. How do you find the numbers?

Answer 1

Tthere are two solutions to a problem:
#(x_1, y_1)=(5,2)#
#(x_2, y_2)=(6/7,-15/7)#

This is a typical problem that can be solved using a system of two equations with two unknown variables.

Let the first unknown variable be #x# and the second #y#.
The difference between them is #3#, which results in the equation: (1) #x-y=3#
Their reciprocals are #1/x# and #1/y#, the sum of which is #7/10#, which results in the equation: (2) #1/x+1/y=7/10# Incidentally, existence of reciprocals necessitates the restrictions: #x!=0# and #y!=0#.
To solve this system, let's use the method of substitution. From the first equation we can express #x# in terms of #y# and substitute into the second equation.
From equation (1) we can derive: (3) #x = y+3#
Substitute it into equation (2): (4) #1/(y+3) + 1/y = 7/10# Incidentally this necessitates another restriction: #y+3!=0#, that is #y!=-3#.
Using common denominator #10y(y+3)# and considering only numerators, we transform equation (4) into: #10y+10(y+3)=7y(y+3)#
This is a quadratic equation that can be rewritten as: #20y+30=7y^2+21y# or #7y^2+y-30=0#
Two solutions to this equation are: #y_(1,2)=(-1+-sqrt(1+840))/14# or #y_(1,2)=(-1+-29)/14#
So, we have two solutions for #y#: #y_1=2# and #y_2=-30/14=-15/7#
Correspondingly, using #x=y+3#, we conclude that there are two solutions to a system: #(x_1, y_1)=(5,2)# #(x_2, y_2)=(6/7,-15/7)#
In both cases #x# is greater than #y# by #3#, so the first condition of a problem is satisfied. Let's check the second condition: (a) for a solution #(x_1, y_1)=(5,2)#: #1/5+1/2=(2+5)/(5*2)=7/10# - checked (b) for a solution #(x_2, y_2)=(6/7,-15/7)#: #7/6-7/15=70/60-28/60=42/60=7/10# - checked

Both solutions are correct.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Let the two numbers be (x) and (x + 3).

The sum of their reciprocals is:

(\frac{1}{x} + \frac{1}{x + 3} = \frac{7}{10})

To solve this equation, first find a common denominator:

(\frac{x + 3}{x(x + 3)} + \frac{x}{x(x + 3)} = \frac{7}{10})

Combine the fractions:

(\frac{x + 3 + x}{x(x + 3)} = \frac{7}{10})

Simplify:

(\frac{2x + 3}{x(x + 3)} = \frac{7}{10})

Cross multiply:

(10(2x + 3) = 7x(x + 3))

Expand:

(20x + 30 = 7x^2 + 21x)

Rearrange into a quadratic equation:

(7x^2 + 21x - 20x - 30 = 0)

Simplify:

(7x^2 + x - 30 = 0)

Factor or use the quadratic formula to find the solutions for (x). Once you find (x), you can find the other number by adding 3 to it.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7